Virtual eStore - VeS.com / Tan Hean Giap - Tan, Hean Giap (2001)
This is an e-commerce project that suitable for medium-scaled company. It allows companies to register as retailer and sell their product online. Customer can choose and compare products' price from different retailer in this system and pay for their products online using credit cards. Before developing this system, surveys on several development tools are carried on. After the literature surveys, appropriate software tools are chosen. Besides, some existing Malaysia e-commerce website also investigated and their weaknesses are identified. Strength of foreign e-commerce is reviewed, hopes that it will help in developing the system. Furthermore, correct methodology of the project is chosen and project planning and scheduling will follow the methodology that was chosen. Then, data flow diagram of the system is prepared. Database system and user interface is design from data flow diagram. At the next step, at the development stage, the system is start coding. Finally, the system is tested and evaluated.